Preparing new normal: the health literacy assessment on the Covid-19 - Supriyati Supriyati; Dian Kurnia Angraeny; Theodora Monica Carissa; Abicintha Pramesti Sheila; Shiefa Annisa Qisthi; Maulidiannisa Rianti; Tommy Roshan (Berita Kedokteran Masyarakat (BKM), 2021)
Purpose: This study was aimed to assess the health literacy of the COVID-19 for both of the knowledge level on the Covid-19 and the health protocol compliance by the medical and the non-medical student. Method: This rapid action research was conducted from July-August 2020. Respondents were Indonesian students who voluntarily fulfilled the online questionnaire. A total 208 respondents participated in this study (104 students for each group). Data analysis was performed by using chi square. Furthermore, an animation video was developed and published through Instagram TV as the follow up assessment. Results: The result showed that the medical students had better knowledge (41.8% vs 33.2%, p-value=0.000) and health protocol compliance (6.3% vs 2.4%, p-value=0.049) than the non-medical students. The lowest compliance towards health protocol of the both groups was the physical distancing. Moreover, the health education regarding physical distancing by using animation video had reached audiences. According to the audiences’ comments, the video made them aware of the importance of physical distancing. Conclusion: It was important to improve health literacy for preparing new normal, and it should be developed based on the need assessment.